Supportive care in cancer patients: recent developments - Karthaus, Meinolf (Antibiotics and chemotherapy, 2000)
An innovation in cancer treatment over the last decade has been the emergence of intensive chemotherapy followed by peripheral blood stem cell transplantation. The success of this intensive chemotherapy also depends on an optimal supportive care, which consists of prevention and management of adverse effects, and psychological support.This book attempts to cover the most frequent problems of supportive care in detail, especially the prevention, diagnosis and treatment of infections, adverse events in the gastrointestinal tract, and the treatment of cytotoxic drug extravasation with special consideration of recently introduced cytotoxic agents. The rational use of hematopoietic growth factors for the reversal of disease- or treatment-related neutropenia, anemia and thrombocytopenia are discussed extensively. Further issues considered include anticoagulant prophylaxis, quality of life and recent advances in the use of effective antiemetics, which have increased the tolerability of standard chemotherapy and radiotherapy, and have opened up new ways of enhancing treatment.Supportive care requires an interdisciplinary approach. This book, therefore, is designed to provide an up-to-date overview for oncologists as well as general physicians, nurses, pharmacists, and all those giving care to cancer patients